Influence of film structure on mobilities of charge carriers in conducting polymers - Harima, Yutaka; Jiang, Xiaoqing; Patil, Rahul; Komaguchi, Kenji; Mizota, Haruo (Electrochimica Acta, 2007)
Two sorts of poly(3-hexylthiophene) (PHT) films with the same chemical compositions were prepared, and their electrochemical, spectroscopic, and transport properties were studied with a special interest in a possible influence of film structure on mobilities of charge carriers. One of the PHT films was electrochemically synthesized using 3-hexylthiophene as a monomer (as-grown film) and the other was obtained by dissolving the as-grown film in chloroform and then casting the polymer solution (cast film). A clear difference was observed in the mobility versus doping level plot between the two sorts of PHT films, demonstrating that the difference is caused only by a distinction in film structure. An initial decreasing feature of the mobility plot observed for the cast films was accounted for in terms of swelling of the films at an early stage of doping. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Doping; electrosynthesis; mobility; poly(3-hexylthiophene); swelling